Implementasi Diversity Program bagi Tenaga Kerja Penyandang Disabilitas pada PT. Wangta Agung Kota Surabaya - Arief Burhan Effendi; Rahaditya Yunianto (Indonesian Journal of Disability Studies, 2017)
This research discusses the implementation of diversity program at PT. Wangta Agung in Surabaya. This research uses qualitative method by interviewing four employees of the company; two employees with disability and two employees without disability. This research uses observation and interview method. The method of analysis is attitude-based method for employees with disabilities. The data of this research were collected through observations and interviews. The result of this research is that the company hires employees with disability that support the value of the organization, apply rules, and provide facilities and infrastructure. The analysis results reveal that the diversity programs are relevant with the employment and organization value for the management of human resource with disabilities. This study shows that the application of diversity program for people with disability on the employees of PT. Wangta Agung in Surabaya has been well managed by the company. The results also show that there is a recruitment system for prospective employees with disabilities.